2010
DOI: 10.1038/ng.543
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple common variants for celiac disease influencing immune gene expression

Abstract: We performed a second-generation genome wide association study of 4,533 celiac disease cases and 10,750 controls. We genotyped 113 selected SNPs with PGWAS<10−4, and 18 SNPs from 14 known loci, in a further 4,918 cases and 5,684 controls. Variants from 13 new regions reached genome wide significance (Pcombined<5×10−8), most contain immune function genes (BACH2, CCR4, CD80, CIITA/SOCS1/CLEC16A, ICOSLG, ZMIZ1) with ETS1, RUNX3, THEMIS and TNFRSF14 playing key roles in thymic T cell selection. A further 13 region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
829
6
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 912 publications
(875 citation statements)
references
References 46 publications
22
829
6
18
Order By: Relevance
“…Three loci did reach a suggestive level of significance ( P  < 2.25 × 10 −5 ). Of particular interest is the chromosome 3 p21.31 region, which is known to be associated with multiple autoimmune diseases such as celiac disease, type 1 diabetes mellitus, and Behçet's disease and is suggestively associated in juvenile idiopathic arthritis (JIA) 35, 36, 37, 38. The strongest association in this region was with rs112088397, which tags a large haplotype block where many additional SNPs reached a suggestive level of significance and is the same risk haplotype as that reported in JIA (r 2  = 0.87) 35, 39.…”
Section: Discussionmentioning
confidence: 99%
“…Three loci did reach a suggestive level of significance ( P  < 2.25 × 10 −5 ). Of particular interest is the chromosome 3 p21.31 region, which is known to be associated with multiple autoimmune diseases such as celiac disease, type 1 diabetes mellitus, and Behçet's disease and is suggestively associated in juvenile idiopathic arthritis (JIA) 35, 36, 37, 38. The strongest association in this region was with rs112088397, which tags a large haplotype block where many additional SNPs reached a suggestive level of significance and is the same risk haplotype as that reported in JIA (r 2  = 0.87) 35, 39.…”
Section: Discussionmentioning
confidence: 99%
“…11,23 In short, this dataset consists of 244 males and 193 females with a mean age of 62 years, who where recruited as controls in a study of gene expression in amyotrophic lateral sclerosis. These control subjects were selected for being in good general health and unaffected for neurological and neurodegenerative diseases; no separate screen for psychiatric disorders was performed for these subjects.…”
Section: Materials and Methods Eqtl Analysis In Controlsmentioning
confidence: 99%
“…Subtle effects of these SNPs on gene expression could be a functional mechanism by which they confer risk for development of schizophrenia. 10,11 Recently, it has been shown that true GWAS hits are enriched for expression QTLs (eQTLs). [11][12][13][14] Therefore, variations influencing gene expression are more likely to be contributing to the phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, multiple genetic loci have been implicated in CD pathogenesis, but their impact on the development of the disease seems to be limited as compared to that of the HLA system. 10 T-cell-mediated immune response plays a crucial role in the pathogenesis of the disease. 11 There is strong evidence that the mucosal lesions of gluten-sensitive enteropathy are initiated within the lamina propria and are due to major histocompatibility complex class 2-expressing activated macrophages that present gliadin peptides to a/ b T-cell receptor CD4 1 lymphocytes.…”
Section: Introductionmentioning
confidence: 99%